Pengaruh Pendelegasian Wewenang dan Pengawasan Terhadap Kinerja - Achmadi Haseran (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
This reseacrh aims to determine the effect of delegation of authority and controlling on employee performance at Sukses Mitra Sejahtera, PT at Kediri district. The population in this research are 584 people, the sampling technique used the Simple Random Sampling and obtained a sample of 85 people. This research uses descriptive statistical analysis method with hypothesis testing using SPSS version 22 software program. Based on the results of the F test, it is proven that the variable delegation of authority and controlling are simultaneously affect employee performance, indicated by a significant value of 0.000 <0.05. The t-test shows that the delegation of authority variable has a partial effect on employee performance. This is indicated by the significant value for delegation of authority variable is 0.150, it means that the possibility of delegation of authority does not affect performance is 15%. The rest there is still an 85% possibility that the delegation of authority has an influence on employee performance and for the controlling variable it has a partial effect on employee performance. This is evidenced by a significance level of 0.001 < 0.05. The coefficient of determination test shows that the value (R Square) is 0.264. It means that the effect of delegation of authority and controlling variables on employee performance is 26,4%. Keywords: Delegation of authority, Controlling, Employee Perfomance